2009
DOI: 10.1002/ange.200900448
|View full text |Cite
|
Sign up to set email alerts
|

Complete Regio‐ and Stereoselectivity Control in the Halohydroxylation of Non‐activated Allenes Mediated by a Remote Sulfinyl Group

Abstract: Keine Hürde ist zu hoch: Die Regio‐ und Stereoselektivität der Halogenhydroxylierung nichtaktivierter Allene wird durch anchimere Unterstützung vonseiten einer entfernten Sulfinylgruppe gesteuert (siehe Schema). Die gebildeten Halogenhydrine sind hervorragende chirale Ausgangsverbindungen für die Herstellung enantiomerenreiner Propargylalkohole und Baylis‐Hillman‐Produkte.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A related, potentially useful observation has been that a remote chiral sulfoxide can control the regio-and stereoselectivity of halohydroxylation in allenes (Scheme 2). [12] Treatment of a variety of g-sulfinylallenes 1 with mixtures of N-bromosuccinimide (NBS)/H 2 O orThe configuration of the sulfinyl is inverted during the reaction; the sulfoxide group attacks the initially formed halonium ion providing intermediate 3, which undergoes ring opening. The authors demonstrated that the products could be transformed into a wide variety of materials.…”
Section: Diastereoselective Halogenation Of Olefinsmentioning
confidence: 99%
“…A related, potentially useful observation has been that a remote chiral sulfoxide can control the regio-and stereoselectivity of halohydroxylation in allenes (Scheme 2). [12] Treatment of a variety of g-sulfinylallenes 1 with mixtures of N-bromosuccinimide (NBS)/H 2 O orThe configuration of the sulfinyl is inverted during the reaction; the sulfoxide group attacks the initially formed halonium ion providing intermediate 3, which undergoes ring opening. The authors demonstrated that the products could be transformed into a wide variety of materials.…”
Section: Diastereoselective Halogenation Of Olefinsmentioning
confidence: 99%
“…Diastereomeric ratios are typically poor (<4:1); however, the products should be readily separable and should provide a way to generate halogenated building blocks in enantiomerically pure form, after auxiliary removal. A related, potentially useful observation has been that a remote chiral sulfoxide can control the regio‐ and stereoselectivity of halohydroxylation in allenes (Scheme ) 12. Treatment of a variety of γ‐sulfinylallenes 1 with mixtures of N ‐bromosuccinimide (NBS)/H 2 O or I 2 /LiOAc/H 2 O in MeCN at 0 °C gave the corresponding bromo‐ and iodohydrin derivatives 2 in high yields (62–99 %) and with excellent diastereoselectivities (up to 98:2).…”
Section: Diastereoselective Halogenation Of Olefinsmentioning
confidence: 99%
“…For simple secondary amines there will be competition between iminium activation and aza-Michael addition under acidic conditions (Scheme 1), and iminium formation is generally favored. We intend to invert this by introducing a remote directing group, [20] so that the carbonyl of the unsaturated ketone is activated and the unstable secondary amine is oriented in a favorable position for the aza-Michael addition.…”
mentioning
confidence: 99%